Loss expression of PHLPP1 correlates with lymph node metastasis and exhibits a poor prognosis in patients with gastric cancer. Issue 7 (26th August 2013) - Wang, Zhixiong; Shu, Haihua; Wang, Zhao; Li, Guanghua; Cui, Ji; Wu, Hui; Cai, Shirong; He, Weiling; He, Yulong; Zhan, Wenhua
ABSTRACT Background PHLPP1 functions as an antitumor factor in several human cancers, but the expression pattern and clinical significance of PHLPP1 in gastric cancer have yet to be determined. The aim of this study is to assess the expression of PHLPP1 in gastric cancer and its impact on the prognosis of patients with gastric cancer. Methods A total of 202 consecutive patients with gastric cancer who had undergone gastrectomy were enrolled in this study. The expressions of PHLPP1 were assessed by immunohistochemistry method. Survival analysis according to PHLPP1 expression was calculated. Results The positive rates of PHLPP1 protein in primary gastric cancer tissues and metastatic lymph nodes were significantly lower than in normal stomach mucosa tissues (56.9% vs. 96.7%, 38.8% vs. 96.7%, both P < 0.001). The overall survival (OS) time and relapse‐free survival (RFS) time in PHLPP1‐positive patients were significantly longer than in PHLPP1‐negative patients (both P < 0.001). Moreover, PHLPP1 was an independent prognostic factor for OS and RFS of gastric cancer patients (HR 0.55, 95% CI 0.36–0.85, P = 0.007; HR 0.52, 95% CI 0.31–0.87, P = 0.013; respectively). Conclusions The loss expression of PHLPP1 was observed in gastric cancer and PHLPP1 is an independent prognostic factor for patients with gastric cancer. J. Surg. Oncol. 2013; 108:427–432. © 2013 Wiley Periodicals, Inc.